Perceived Value, E-Trust, E-Satisfaction, and E-Loyalty on Online Trip Clients in Jakarta - Kalim, Muchamad Nur; Prasetyo, Wisnu Budi; Ramli, Abdul Haeba; Mariam, Siti (Institut Ilmu Sosial dan Manajemen STIAMI, 2024)
In the realm of internet technology that has occurred in Indonesia, it has had an impact on the trip business sector, since the presence of online trip agents, the market potential for the trip business has increased. This investigation points out to explore how Perceived Value and E-Trust influence E-Loyalty by using the E-Satisfaction variable as an intercede variable. This investigation was conducted on 110 respondents who had used online trip in Jakarta. Data analysis in this investigation used SEM-PLS. The conclusion of this investigation shows that Perceived Value has a positive effect on E-Satisfaction, E-Trust has a positive effect on E-Satisfaction, E-Satisfaction has a positive effect on E-Loyalty, Perceived Value has a positive effect on E -Loyalty, while E-Trust has a negative effect on E-Loyalty, E-Trust has a negative effect on E-Loyalty through E-Satisfaction and Perceived Value has a negative effect on E-Loyalty through E-Satisfaction. Suggestions in this investigation are to add investigation variables and use different investigation methods. The managerial implication obtained is that online trip agent companies must pay attention to the perceived value and e-trust of clients towards the corporation in order to create e-Satisfaction for clients. When e-Satisfaction is achieved, the corporation must maintain it to achieve e-loyalty.